2004
DOI: 10.21273/hortsci.39.5.1062
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of 1-Methylcyclopropene on `Cortland' and `McIntosh' Apple Quality Following Long-term Storage

Abstract: `Redcort Cortland' and `Redmax' and `Summerland McIntosh' apples (Malus ×domestica Borkh.) were treated with 900 nL·L-1 of 1-methylcyclopropene (1-MCP) for 24 hours at 20 °C before storage and were kept at 3 °C in either a controlled atmosphere (CA) of 2 kPa O2 and <2.5 kPa CO2 or in an air (RA) environment for up to 9 months. After 4.5 months, half of the fruit were treated with a se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
35
0
3

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(42 citation statements)
references
References 12 publications
3
35
0
3
Order By: Relevance
“…SSC was very close to the plot centre and was poorly related to 1‐MCP treatment. The multivariate data obtained in this cultivar confirmed the literature and showed that firmness may be considered as the most important parameter discriminating the treated and untreated fruits 9–12. The results concerning acidity were in concordance to those obtained in other apple cultivars 13.…”
Section: Discussionsupporting
confidence: 87%
“…SSC was very close to the plot centre and was poorly related to 1‐MCP treatment. The multivariate data obtained in this cultivar confirmed the literature and showed that firmness may be considered as the most important parameter discriminating the treated and untreated fruits 9–12. The results concerning acidity were in concordance to those obtained in other apple cultivars 13.…”
Section: Discussionsupporting
confidence: 87%
“…6A). Crouch (2003) observed no differences in the firmness of 1‐MCP‐treated pear fruits immediately after removal from cold storage, but significant firmness retention in 1‐MCP‐treated apples immediately exiting cold storage has been observed (Zanella 2003; Delong et al. 2004; Bai et al.…”
Section: Resultsmentioning
confidence: 99%
“…In both maturity stages, the highest 1‐MCP dose was the most effective treatment in maintaining elasticity. According to the more recent studies, 1‐MCP was effective in delaying fruit softening in various horticultural products such as tomatoes,10, 14, 15, 27 apple,28–31 plum32, 33 and apricot34, 35. Softening is thought to be associated with the degradation of pectic substance in the cell wall caused by accumulation of cell wall hydrolase activities such as pectinesterase (PE), PG and β‐galactosidase (β‐Gal) 36–38.…”
Section: Discussionmentioning
confidence: 99%